2023
DOI: 10.1038/s43856-023-00325-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral factors and SARS-CoV-2 transmission heterogeneity within a household cohort in Costa Rica

Kaiyuan Sun,
Viviana Loria,
Amada Aparicio
et al.

Abstract: Introduction Variability in household secondary attack rates and transmission risks factors of SARS-CoV-2 remain poorly understood. Methods We conducted a household transmission study of SARS-CoV-2 in Costa Rica, with SARS-CoV-2 index cases selected from a larger prospective cohort study and their household contacts were enrolled. A total of 719 household contacts of 304 household index cases were enrolled from November 21, 2020, through July 31, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The results of the household transmission study have been published. 18 We detected a seroprevalence of 53% among household members of our index cases, with an estimated household secondary attack rate of 34%. Mask wearing by the index cases was strongly protective against transmission to the household.…”
Section: Findings To Datementioning
confidence: 66%
See 1 more Smart Citation
“…The results of the household transmission study have been published. 18 We detected a seroprevalence of 53% among household members of our index cases, with an estimated household secondary attack rate of 34%. Mask wearing by the index cases was strongly protective against transmission to the household.…”
Section: Findings To Datementioning
confidence: 66%
“…Characteristics or behaviour of the index cases were considered determinants of transmission, while characteristics of the household members were considered determinants of susceptibility. The results of the household transmission study have been published 18…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…26 For example, policies providing appropriate and cost-free isolation for essential workers would have prevented chains of Covid-19 transmission to higher-risk people who resided in multi-generation households, especially during pre-vaccine and pre-therapeutic eras. [27][28][29] Similarly, efforts to increase vaccination uptake and implement effective therapeutics among at-risk populations would have reduced disparities. 23,[30][31][32][33][34][35][36] For the overall population and among all adults (>25 years), existing race/ethnicity mortality disparities widened at the onset of the pandemic and during Covid-19 waves but narrowed during the vaccine era.…”
Section: Discussionmentioning
confidence: 99%
“…Previous COVID-19 transmission studies have shown that sharing a bedroom with the index individual significantly increases transmission risk, while self-reported mask wearing by contacts or the index individual significantly decreases transmission risk [ 8 , 9 ]. In a PEP study, differences in household demographics, the severity of an index individual’s illness, and their interactions with household members can lead to very different risks of transmission within the household.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies primarily assessing COVID-19 transmission often enroll both the index individuals and their contacts [ 6 , 7 ], to our knowledge no studies assessing COVID-19 PEP have enrolled index individuals because they do not directly inform the efficacy of prevention interventions. However, the severity of an index individual’s illness and their interaction with household members are important predictors of infection in their household contacts [ 8 , 9 ], and adjusting for prognostic covariates such as these can increase the precision of PEP efficacy estimates [ 10 ].…”
Section: Introductionmentioning
confidence: 99%